IMPROVEMENT OF THE ASSESSMENT CRITERIA FOR SCIENTIFIC RESEARCH PROJECTS - A PREMISE OF INCREASING THE UNIVERSITY SCIENTIFIC RESEARCH PERFORMANCE - Cristian Marius TOMA; Vasilica TOMA; Dumitru ZAIȚ (SEA: Practical Application of Science, 2013)

(untitled)
The National Plan for Research, Development and Innovation 2007 – 2013, called herein the National Plan II, represents the main instrument used to implement the National Strategy for Research, Development and Innovation. Universities play a unique role in the development of the knowledge-based society, through its contribution to knowledge generation, transmission, dissemination and utilization. The essential role of the university is to shape the highly qualified human resource, a process that implies a symbiosis between the education and research, the education system performances contributing in this way to a great extent to the society development. The highly qualified human resource represents an important asset of a nation. This study is dedicated to the analysis of the assessment criteria for the Exploratory Research Projects (ERP) handed in the competitions in 2007, 2008, 2011 and 2012 and to highlight the importance of improving the assessment criteria in order to improve their quality.